2019
DOI: 10.1007/s10578-019-00933-1
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in Children with Selective Mutism: A Meta-analysis

Abstract: This study evaluates the current conceptualization of selective mutism (SM) as an anxiety disorder in the DSM-5 using a meta-analytic approach. In the absence of any systematic assessment of anxiety in the field of SM, we pooled prevalence data of comorbid anxiety disorders in a random-effects meta-analysis. On the basis of 22 eligible studies (N = 837), we found that 80% of the children with SM were diagnosed with an additional anxiety disorder, notably social phobia (69%). However, considerable heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 73 publications
6
41
1
4
Order By: Relevance
“…While the role of anxiety in SM is clear (e.g., Driessen et al 2020;Muris and Ollendick 2015;Sharp et al 2007;Viana et al 2009), the purpose of the present review is to suggest that-in some children with SM-ASD seems to be present as well. We have pointed out that on a categorical and dimensional level-relations among SM, SAD, and ASD are substantial and they can be considered to be a unified trinity of social disorders.…”
Section: Sm: More Than Just An Anxiety Disorder?mentioning
confidence: 89%
See 1 more Smart Citation
“…While the role of anxiety in SM is clear (e.g., Driessen et al 2020;Muris and Ollendick 2015;Sharp et al 2007;Viana et al 2009), the purpose of the present review is to suggest that-in some children with SM-ASD seems to be present as well. We have pointed out that on a categorical and dimensional level-relations among SM, SAD, and ASD are substantial and they can be considered to be a unified trinity of social disorders.…”
Section: Sm: More Than Just An Anxiety Disorder?mentioning
confidence: 89%
“…Ibi and Leo were referred to an outpatient facility specialized in the treatment of childhood anxiety disorders. These referrals seemed appropriate given the prominent role of anxiety, and in particular social anxiety, in the clinical picture of this psychiatric disorder (e.g., Driessen et al 2020 ; Muris and Ollendick 2015 ), which has resulted in its allocation to the category of anxiety disorders in current versions of classification systems including the Diagnostic and Statistical Manual of Mental Disorders (DSM-5; APA 2013 ) and the International Classification of Diseases (ICD-11; World Health Organization [WHO] 2018 ). A standardized questionnaire taken at the clinic confirmed the presence of anxiety problems and revealed clinically elevated scores, not only for social anxiety (both boys), but also for a number of other anxiety problems such as separation anxiety (Ibi), generalized anxiety (Leo), and specific phobias (both boys).…”
Section: Introductionmentioning
confidence: 99%
“…This decision was based on a significant number of studies indicating anxiety as a central phenomenon of SM, a common etiology between SM and other anxiety disorders, and results from initial treatment studies [4,8,9]. High comorbidity rates between SM and other anxiety disorders, in particular with social anxiety disorders (SAD), have been found [9][10][11]. Etiologically, behavioral inhibition (BI) was found to display a significant role for anxiety disorders in general and for SM in particular.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published meta-analysis nicely summarizes the results of 22 studies in which clinical interviews were conducted in children with SM to establish the co-occurrence of other anxiety disorders. 9 The results showed that 80% of the children with SM also fulfilled the diagnostic criteria for at least one other anxiety disorder, and in the vast majority of cases (69%) this involved social anxiety disorder (SAD). A second line of inquiry has focused on the content of the fears and fear-related cognitions of children with SM.…”
Section: Empirical Evidence On the Link Between Sm And (Social) Anxiementioning
confidence: 99%